Isolasi Senyawa Kimia Stigmastan-3,5-Diena Yang Mempunyai Daya Toksik Dari Daun Ekaliptus (Eucalyptus Deglupta Blume.) - Sari Setianingsih; Rudi Kartika; Partomuan Simanjuntak (JURNAL KIMIA MULAWARMAN, 2017)
This study was started by extraction of Eucalyptus deglupta Blume. Using organic solvent (n-hexane, ethyl acetate, ethanol and water) followed by phytochemical screening and toxicity test using Brine Shrimp Lethality Test (BSLT) method. Isolation and identification of chemical compounds contained in the fraction were done by column chromatography and Gas Chromatography-Mass Spectrometry (GC-MS) analysis. Phytochemical screening revealed the presence of alkaloids, flavonoids, steroids and phenolics in the extract. Toxicity test results showed that the ethyl acetate extract was potentially active with LC50 value of 617.95 ppm. The extract was continued to isolation stage and gave fraction EKEA-3.1 with LC50 value of 2759.93 ppm. Identification of chemical compounds in EKEA-3.1 with KG-MS analysis showed that EKEA-3.1 was suspected to be Stigmastan-3,5-diene.